Early screening of cassava for resistance to rootknot nematodes - Kagoda, F.; Coyne, D.; Kajumba, C.; Dusabw, J. (2004)
Two node cuttings of 18 cassava varieties were planted in 20 cm diameter non-disposable plastic pipes filled with sawdust with the objective of establishing their resistance to root knot nematodes (Meloidogyne spp.). The cassava plants were left to grow for one month after which they were inoculated with 1000 eggs of Meloidogyne spp. Plants were left to grow for another two months after inoculation before assessment. The trial was repeated three times and data pooled for analysis. Greater resistance to root knot nematodes was observed in the cultivars TME 12, Migyera, Nase 10 and TME 5. Cultivars Nase 1, TME 12, 192/0232, Abbey and TME 4 had moderate resistance. These varieties were characterised by low galling index, high plant heights and high fresh root weights. Cultivars TME 14 and P.D.B showed tolerance to root knot nematodes. Varieties, MH 95/0414, 95/SE00087, MM96/0245, 94/SE00036 and MM96/0561, respectively had more than 50% roots galled coupled with low fresh root weights or rotten roots hence, highly susceptible to root knot nematodes. Though varieties 192/0427 and 191/0057 exhibited low galling index, their fresh root weights remained low hence highly susceptible. Meloidogyne spp. populations did not significantly differ across varieties probably because of the short time duration.